Proceedings of the 42nd International ACM SIGIR Conference on Research and Development in Information Retrieval 2019
DOI: 10.1145/3331184.3331319
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-Aware Clinical Abstractive Summarization

Abstract: Automatically generating accurate summaries from clinical reports could save a clinician's time, improve summary coverage, and reduce errors. We propose a sequence-to-sequence abstractive summarization model augmented with domain-specific ontological information to enhance content selection and summary generation. We apply our method to a dataset of radiology reports and show that it significantly outperforms the current state-of-the-art on this task in terms of rouge scores. Extensive human evaluation conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Zhang et al (2018) first studied the problem of automatic generation of radiology impressions by summarizing textual radiology findings, and showed that an augmented pointer-generator model achieves high overlap with human references. MacAvaney et al (2019) extended this model with an ontologyaware pointer-generator and showed improved summarization quality. Li et al (2019) and studied generating textual descriptions of radiology findings from medical images, and proposed RL-based approaches to tackle this problem.…”
Section: Related Workmentioning
confidence: 99%
“…Zhang et al (2018) first studied the problem of automatic generation of radiology impressions by summarizing textual radiology findings, and showed that an augmented pointer-generator model achieves high overlap with human references. MacAvaney et al (2019) extended this model with an ontologyaware pointer-generator and showed improved summarization quality. Li et al (2019) and studied generating textual descriptions of radiology findings from medical images, and proposed RL-based approaches to tackle this problem.…”
Section: Related Workmentioning
confidence: 99%
“…having all major information, or missing key points. Figure . 2 presents the human evaluation results using histograms and arrow plots as done in (MacAvaney et al, 2019), comparing our system's Impressions versus human-written Impressions. The histograms indicate the distribution of scores, and arrows show how the scores changed between ours and human-written.…”
Section: Expert Evaluationmentioning
confidence: 99%
“…Recently, there has been growing interest in applying the capacity of AI to investigate specific datasets in medical fields [42][43][44][45][46][47][48][49] . AI has special image processing capabilities to discern multi-faceted features that would otherwise elude trained pathologists.…”
Section: Introductionmentioning
confidence: 99%